Microstructure thermostability of shot peened duplex stainless steel surface layer. (June 2013) - Feng, Q; Jiang, C H; Xu, Z; Wu, X Y
Abstract : Shot peening treatment was employed to introduce deformation into the surface layer of duplex stainless steel S32205, and the microstructure thermostability during isothermal annealing was investigated using X-ray diffraction line profile analysis. Microstructure variation in shot peened layer is observed with the extension of annealing time. The domain growth activation energy and microstrain relaxation energy in both ferrite and austenite were calculated by computer regression analysis. Compared to ferrite, the shot peened austenite exhibits a higher dislocation density, a larger driving force for recrystallisation and relaxation; however, it has higher activation energy of domain growth and higher microstrain relaxation energy. The results show that the microstructure thermostability of austenite is higher than that of ferrite.